Structural controls of auriferous reefs at Fairview Mine, Barberton Greenstone Belt, South Africa - Gloyn-Jones, Jonathan (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.